Living and training at 825 m for 8 weeks supplemented with intermittent hypoxic training at 3,000 m improves blood parameters and running performance - Wonnabussapawich, P.; Hamlin, M. J.; Lizamore, C. A.; Manimmanakorn, N.; Leelayuwat, N.; Tunkamnerdthai, O.; Thuwakum, W.; Manimmanakorn, A. (The Journal of Strength and Conditioning Research, 2017)
We aimed to investigate the effect of an 8-week low-altitude training block supplemented with intermittent hypoxic training, on blood and performance parameters in soccer players. Forty university-level male soccer players were separated into altitude (n = 20, 825 m) or sea-level (n = 20, 125 m) groups. Before (1-2 days ago) and after (1 and 14 days later) training, players were asked to give a resting venous blood sample and complete a series of performance tests. Compared with sea level, the altitude group increased erythropoietin, red blood cell (RBC) count, and hematocrit 1 day after training (42.6 ± 24.0%, 1.8 ± 1.3%, 1.4 ± 1.1%, mean ± 95% confidence limits (CL), respectively). By 14 days after training, only RBC count and hemoglobin were substantially higher in the altitude compared with the sea-level group (3.2 ± 1.8%, 2.9 ± 2.1% respectively). Compared with sea level, the altitude group 1-2 days after training improved their 50-m (-2.9 ± 1.4%) and 2,800-m (-2.9 ± 4.4%) run times and demonstrated a higher maximal aerobic speed (4.7 ± 7.4%). These performance changes remained at 14 days after training with the addition of a likely higher estimated VO2max in the altitude compared with the sea-level group (3.2 ± 3.0%). Eight weeks of low-altitude training, supplemented with regular bouts of intermittent hypoxic training at higher altitude, produced beneficial performance improvements in team-sport athletes, which may increase the viability of such training to coaches and players that cannot access more traditional high altitude venues.